Antarctophthirus trichechi Bohemann 1865 - Leonardi, Maria Soledad; Palma, Ricardo Luis (Zenodo, 2013)
Antarctophthirus trichechi (Bohemann, 1865) Haematopinus Trichechi Bohemann, 1865: 577, pl. 35, figs 2, 2a,b. Haematopinus trichechi Bohemann, 1865; Piaget 1880: 656; Breddin 1901: 557; King 1964: 139. Haematopinus tricheci [sic] Bohemann, 1865; Dalla Torre 1908: 11. Misspelling. Antarctophthirus trichechi (Bohemann, 1865); Enderlein 1909: 508, 512, pls 55–56, pl. 60, figs 185–188; Neumann 1909: 532, figs 30–31; Kellogg & Ferris 1915: 49, fig. 17B, pl. 3, fig. 1; Ferris 1916a: 183; Cummings 1916: 172; Fahrenholz 1917: 5; Freund 1928: 25, figs 24–29; Ferris 1934: 492, figs 287–288; Maltbaek 1937: 20; Thompson 1938: 94; Herms 1939: 105; Eichler 1941: 375, fig. 34; Hopkins 1949: 509; Weber 1950: 172; Ferris 1951: 75; Blagoveshtchensky 1958: 377; Scherf 1963: 17, figs 1–6, 19–20; Blagoveshtchensky 1964: 326; King 1964: 139; Spencer 1966: 23; Margolis & Dailey 1972: 14; Kaisila 1973: 64; Kim et al. 1975: 547; King 1983: 203; Kim et al. 1986: 48, pl. 3; Zarubina 1986: 373; Kim 1988: 108; Durden & Musser 1994a: 7; Durden & Musser 1994b: 140; Jensen & Palma 2005: 227, fig. 5.32c. Arctophtirius trichechi (Bohemann, 1865); Mjöberg 1910: 178, 259, figs 89–92, 154. Antarctophthirius [sic] trichechi (Bohemann, 1865); Ass 1934: 94, 103, figs 2–13. Misspelling. Antarctophthirius [sic] trichoechi [sic] (Bohemann, 1865); Ass 1963: 6, figs 2–5. Misspellings. Antarctophthirus tricechi [sic] (Bohemann, 1865); Coulson & Refseth 2004: 96. Misspelling. Type host. Odobenus rosmarus (Linnaeus, 1758) —Walrus. Type locality. Spitsbergen Island, Hinlopen Strait, Norway. Type specimen/s data. None designated, repository unknown. Probably lost. Other hosts. None. Geographic distribution. Arctic Region. Significant references. Freund (1928: 25, detailed figures); Ferris (1934: 492, synonymy, description, figures, hosts); Ass (1934: 94, descriptions and figures of adults, egg, and nymphs); Scherf (1963: 17, descriptions of eggs, nymphs and adults); Kim et al. (1986: 48, redescription, figures); Durden & Musser ...